Application Software Reengineering. - Alam, M. Afshar (2010)
The book is about reorganizing and modifying existing software systems to make them more maintainable and user friendly. It also powerfully dwells on the aspects of general Application Software Reengineering across various fields.
12.7 Applications of Program Slicing.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books